MOLECULAR CHARACTERIZATION OF MUTANT STRAINS OF CALOCYBE INDICA USING RAPD-PCR - JATINDER KAUR; HARPREET S. SODHI (The Bioscan, 2012)
Tremendous revolution in the mushroom technology in recent years with respect to types and strains of cultivated mushrooms has made Calocybe indica, a specialty mushroom, the third most popular and commercially grown mushroom in India. A lot of work has been done as far its cultivation technology is concerned but no systematic work has been undertaken for its genetic improvement. During present investigation improvement of high yielding strain, Ci-3 using mutagenic treatment on protoplasts was conducted. Four mutagenic treatments (Ultraviolet rays, N-methyl-N’-nitro-N-nitrosoguanidine, Ethidium bromide and 5'-Bromouracil) yielded 30 putative mutants. Seven mutants were identified on the basis of growth and enzymes studies. Molecular characterization of the seven selected mutant strains was conducted using RAPD technique. A set of 14 primers were used for molecular characterization of mutants along with the parent. Out of these only 6 primers resulted gave distinct amplification products. Six primers yielded 68 scorable bands ranging from 40bp to 280bp. No two genotypes showed 100% similarity between them. Maximum similarity coefficient of value 0.897 was obtained between CMN-9 and CMB-4. Minimum similarity coefficient (0.617) was found between CMU-5 and CMN-11. Similarity coefficient of Ci-3 ranged from 0.706 for CMN-3 to 0.794 for CMU-2.